Transgenic Drosophila for Investigating DUX4 and FRG1, Two Genes Associated with Facioscapulohumeral Muscular Dystrophy (FSHD). - Takako I Jones; Megan Parilla; Peter L Jones (PLoS ONE)
Facioscapulohumeral muscular dystrophy (FSHD) is typically an adult onset dominant myopathy. Epigenetic changes in the chromosome 4q35 region linked to both forms of FSHD lead to a relaxation of repression and increased somatic expression of DUX4-fl (DUX4-full length), the pathogenic alternative splicing isoform of the DUX4 gene. DUX4-fl encodes a transcription factor expressed in healthy testis and pluripotent stem cells; however, in FSHD, increased levels of DUX4-fl in myogenic cells lead to aberrant regulation of target genes. DUX4-fl has proven difficult to study in vivo; thus, little is known about its normal and pathogenic roles. The endogenous expression of DUX4-fl in FSHD-derived human muscle and myogenic cells is extremely low, exogenous expression of DUX4-fl in somatic cells rapidly induces cytotoxicity, and, due in part to the lack of conservation beyond primate lineages, viable animal models based on DUX4-fl have been difficult to generate. By contrast, the FRG1 (FSHD region gene 1), which is linked to FSHD, is evolutionarily conserved from invertebrates to humans, and has been studied in several model organisms. FRG1 expression is critical for the development of musculature and vasculature, and overexpression of FRG1 produces a myopathic phenotype, yet the normal and pathological functions of FRG1 are not well understood. Interestingly, DUX4 and FRG1 were recently linked when the latter was identified as a direct transcriptional target of DUX4-FL. To better understand the pathways affected in FSHD by DUX4-fl and FRG1, we generated transgenic lines of Drosophila expressing either gene under control of the UAS/GAL4 binary system. Utilizing these lines, we generated screenable phenotypes recapitulating certain known consequences of DUX4-fl or FRG1 overexpression. These transgenic Drosophila lines provide resources to dissect the pathways affected by DUX4-fl or FRG1 in a genetically tractable organism and may provide insight into both muscle development and pathogenic mechanisms in FSHD.